Obesity as a risk factor of COVID-19 severity: A literature review - Pradana, Krisnanda Aditya; Ellina, Agusta Dian (International journal of health sciences, 2022)
Backgrounds: Patients with underlying comorbidities are more prone to contracting COVID-19 and developing severe and clinically deteriorating disease than patients without previous comorbidities. Obesity is a comorbid disease of COVID-19 with a high prevalence and is associated with the severity of COVID-19. This study aims to know about obesity as a risk factor of COVID-19 Severity. Methods/Design: This research method is literature review. The data bases used include Pubmed, DOAJ, and Wiley in the period 2016 until 2020. The keywords used in this article search is obesity, severity, and Covid-19. Based on the keywords used, 3,271 related articles were obtained. Based on the results of the article search process from various databases, 10 relevant articles were obtained. Conclusion: From the systematic review study obtained, it shows that obesity is a risk factor of COVID-19 severity.